S100A8 and S100A9: DAMPs at the Crossroads between Innate Immunity, Traditional Risk Factors, and Cardiovascular Disease - Alexandru Schiopu; Ovidiu S. Cotoi (Hindawi Limited, 2013)
Amplification of innate immune responses by endogenous danger-associated molecular patterns (DAMPs) promotes inflammation. The involvement of S100A8 and S100A9, DAMPs belonging to the S100 calgranulin family, in the pathogenesis of cardiovascular disease is attracting an increasing amount of interest. S100A8 and S100A9 (also termed MRP8 and MRP14) preferentially form the S100A8/A9 heterodimer (MRP8/14 or calprotectin) and are constitutively expressed in myeloid cells. The levels of circulating S100A8/A9 in humans strongly correlate to blood neutrophil counts and are increased by traditional cardiovascular risk factors such as smoking, obesity, hyperglycemia, and dyslipidemia. S100A8/A9 is an endogenous ligand of toll-like receptor 4 (TLR4) and of the receptor for advanced glycation end products (RAGE) and has been shown to promote atherogenesis in mice. In humans, S100A8/A9 correlates with the extent of coronary and carotid atherosclerosis and with a vulnerable plaque phenotype. S100A8/A9 is locally released following myocardial infarction and amplifies the inflammatory responses associated with myocardial ischemia/reperfusion injury. Elevated plasma levels of S100A8/A9 are associated with increased risk of future coronary events in healthy individuals and in myocardial infarction survivors. Thus, S100A8/A9 might represent a useful biomarker and therapeutic target in cardiovascular disease. Importantly, S100A8/A9 blockers have been developed and are approved for clinical testing.